A comparison between the effects of metformin and N-acetyl cysteine (NAC) on some metabolic and endocrine characteristics of women with polycystic ovary syndrome. (2nd April 2016) - Javanmanesh, Forough; Kashanian, Maryam; Rahimi, Maryam; Sheikhansari, Narges
Abstract: Objective : To compare N -acetyl cysteine (NAC) and metformin on polycystic ovary syndrome (PCOS). Method : Study was performed as a randomized double-blind clinical trial on women with diagnosis of PCOS without additional complications. In one group, oral NAC 600 mg, three times a day and in the other group, 500 mg oral metformin, three times a day were prescribed. Duration of treatment was 24 weeks, and after finishing this period of treatment, fasting blood glucose (FBS) and insulin, lipid profile and Homeostasis Model Assessment (HOMA) index were measured (all the blood samples were taken while fasting) and were compared in the two groups. Results : Forty-six women in NAC group and 48 women in metformin group finished the study. The two groups did not show significant difference according to age, body mass index (BMI) of more than 30; mean BMI, AUB, FBS, fasting blood insulin, lipid profile and HOMA index before treatment. After 24 weeks of treatment; BMI >30 [17 (35.4%) versus 7 (15.2%), p  = 0.033], mean BMI [(28.36 ± 2.27) versus (27.11 ± 3.55), p  = 0.44], number of women with the complain of abnormal uterine bleeding (AUB) [24 (50%) versus 13 (28.3%), p  = 0.037], FBS [(90.02 ± 6.24) versus (86.61 ± 7.81), p  = 0.021], fasting insulin (10.40 ± 2.64 versus 8.89 ± 2.20, p  = 0.004), HOMA Index (2.09 ± 0.69 versus 1.71 ± 0.45, p  = 0.001), low density lipoprotein (LDL) (141.83 ± 26.98 versus 127.89 ± 28.70, p  = 0.017) were less in NAC group. Triglyceride (TG) and total cholesterol did not show significant difference between the two groups after treatment. High-density lipoprotein (HDL) was higher in NAC group. Conclusion : NAC can improve lipid profile and fasting blood sugar (FBS) and fasting blood insulin better than metformin.